Investigating the factors that influence patients’ waiting time at an outpatient department of a tertiary hospital in Saudi Arabia - Abrahams, Moira (Stellenbosch : Stellenbosch University, 2022)
Thesis (MNur)--Stellenbosch University, 2022.